Histomorphological Study and Scanning Electron Microscopy of the Duodenum in the Iraqi Black Partridge (Francolinus francolinus) - Ola Al-Bhadly (Journal of Global Pharma Technology, 2018)
Objective: This project aimed to study the Morphological description and histological structure by using light and scanning electron microscope of duodenum in both male and female Iraqi black partridge (Francolinus francolinus) Methods: To conduct this investigation, 20 healthy Iraqi black partridge were collected from local suppliers. Birds were euthanized, dissected and then specimens were processed for histological and histochemical staining techniques. Results: Morphological study showed the duodenum consists of descending and ascending limbs forming (U) shaped tube called duodenal loop extend from the right side of the dorsal surface of the gizzard. The pancreatic and bile ducts opened in the end of the ascending limb. Male had significantly higher than Female in the mean length and weight of duodenum. Histologically, the wall of the duodenum was consisted of four tunicae mucosa, submucosa, muscularis and serosa. The mucosa had a distinctive feature by the presence of villi had finger shape and the crypts of lieberkuhn which covered by simple columnar epithelium with goblet cells. The goblet cells gave positive reaction with PAS stain. Duodenal villi appeared by SEM very long and finger-like shaped with two organized orientations, primary and secondary villi. No significant differences between sexes in the villi height, crypts depth and the number of goblet cells but significantly difference in the mean thickness of tunica. Conclusion: the results showed that the significant difference in the mean length, weight of duodenum and thickness of tunica between two the sexes may be related to differences in food intake amounts. Goblet cells neutral mucopolysaccharide secretions; in fact, the latter stain is an indicator mucin substance which are very important in digestion and absorption and subsequent body growth of the bird.Keywords: Duodenum, Histomorphology, IRAQI Black Partridge, Scanning electron microscope.